A kind of anti-bending data connection line and its preparation method

Through the combination of modified resin and modified filler, the problem of easy damage to traditional data connection lines during bending is solved, and higher bending resistance and service life are achieved.

CN119340030BActive Publication Date: 2025-04-15JIANGXI SHENGYING TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411898735.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-15
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

Traditional data connection lines are prone to physical damage during frequent bending and use, resulting in unstable transmission or complete failure, affecting the device's experience and service life.

Method used

The modified resin is used as the protective layer, and polyurethane prepolymer is formed by reaction of polypropylene glycol and isophorone diisocyanate, and the end is blocked with -2-hydroxyethyl methacrylate, and combined with PVC paste resin and modified filler for in-depth refining to form a bending-resistant data connection line.

Benefits of technology

It improves the bending resistance of the data connection wire, extends the service life, enhances the protection of internal conductors, and ensures the stability of data transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an anti-bending data connecting line and a preparation method thereof, and relates to the technical field of data line preparation. Polyethylene is coated on the surface of a conductor to form an insulating layer, a braided layer is arranged outside the insulating layer, a shielding layer is arranged outside the braided layer, and a modified resin is coated outside the shielding layer to form a protective layer to prepare the anti-bending data connecting line. The modified resin is prepared from the following raw materials: PVC paste resin, modified polyurethane, allyl alcohol glycidyl ether, dioctyl phthalate, trimethylolpropane trimethacrylate, modified filler and 4,4'-diaminodiphenylmethane banburying. The modified filler has a special core-shell structure with carbon nanotubes as a hard core, polyborosiloxane coating as a soft layer, and polymethyl methacrylate as a hard shell. When subjected to external force, the shell layer in the modified filler can cause cracks to deflect when reaching the core-shell interface, and the deflection of the crack increases the path of crack expansion, thereby absorbing energy and improving the toughness of the modified resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of data line preparation, and in particular to a bending-resistant data connection line and a preparation method thereof. Background Art

[0002] In modern electronic devices, data transmission is one of the indispensable functions. Traditional data cables are prone to physical damage during frequent bending and use, resulting in unstable transmission or complete failure, affecting the user experience and service life of the device. Especially for portable electronic devices that are carried and used more frequently in daily life, such as smartphones, laptops, and wearable technologies, flexible and durable data cables have become one of the important needs of users. The outer shell of the data cable is usually polyvinyl chloride, but polyvinyl chloride is not very flexible. Long-term or repeated bending will cause the outer shell to break, which will in turn make it impossible to protect the internal wires, affecting the service life of the data transmission cable. Summary of the invention

[0003] The purpose of the present invention is to provide a bending-resistant data connection line and a preparation method thereof, which solves the problem that the shell of the data line may be damaged after repeated use at present.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing a bending-resistant data connection line comprises the following steps:

[0006] Step A1: polypropylene glycol and isophorone diisocyanate are mixed, nitrogen is introduced for protection, dibutyltin dilaurate is added under stirring at a speed of 120-150 r / min and a temperature of 85-90° C., and the mixture is reacted for 2-3 hours, and then 2-hydroxyethyl methacrylate and hydroquinone are added and reacted for 2-4 hours to obtain a modified polyurethane;

[0007] Step A2: PVC paste resin, modified polyurethane, allyl alcohol glycidyl ether, dioctyl phthalate and trimethylolpropane trimethacrylate are mixed uniformly, placed at a temperature of 25-30° C. for 40-45 hours, heated to 150-155° C., kept warm for 10-15 minutes, placed in an internal mixer, modified filler and 4,4'-diaminodiphenylmethane are added, and the mixture is internally kneaded at a temperature of 170-180° C. for 20-30 minutes to obtain a modified resin;

[0008] Step A3: polyethylene is coated on the surface of the conductor to form an insulating layer, a braided layer is provided outside the insulating layer, a shielding layer is provided outside the braided layer, and a modified resin is coated outside the shielding layer to form a protective layer, so as to obtain a bending-resistant data connection line.

[0009] Furthermore, the molar ratio of polypropylene glycol, isophorone diisocyanate and 2-hydroxyethyl methacrylate in step A1 is 1:2.5:3.2, the amount of dibutyltin dilaurate is 2% of the total mass of polypropylene glycol, isophorone diisocyanate and 2-hydroxyethyl methacrylate, the amount of hydroquinone is 1‰ of 2-hydroxyethyl methacrylate, and the molecular weight of polypropylene glycol is 400.

[0010] Furthermore, the weight ratio of the PVC paste resin, modified polyurethane, allyl alcohol glycidyl ether, dioctyl phthalate, trimethylolpropane trimethacrylate, modified filler and 4,4'-diaminodiphenylmethane described in step A2 is 100-120:20-30:10-15:10-12:20-30:10-15:3-5.

[0011] Further, the modified filler is prepared by the following steps:

[0012] Step B1: octamethylcyclotetrasiloxane, tetramethyltetrasiloxane, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, tetramethylammonium hydroxide and DMF are uniformly mixed, and reacted for 2-3 hours at a speed of 150-200 r / min and a temperature of 105-110° C. to obtain intermediate 1; intermediate 1, 1,2-epoxydodecane and DMF are uniformly mixed, and reacted for 3-5 hours at a speed of 120-150 r / min, a temperature of 60-70° C. and a pH value of 10-11 to obtain intermediate 2;

[0013] The reaction process is as follows:

[0014]

[0015] Step B2: 4-formylphenylboronic acid, diaminobutene, triethylamine and DMF are mixed, and the reaction is carried out for 3-5 hours at a speed of 200-300 r / min and a temperature of 20-25°C to obtain intermediate 3. Carbon nanotubes are dispersed in ethanol, and KH570 and deionized water are added under stirring at a speed of 200-300 r / min and a temperature of 60-70°C, and the reaction is carried out for 1-1.5 hours to obtain modified carbon nanotubes. The modified carbon nanotubes, intermediate 2, chloroplatinic acid and DMF are uniformly mixed, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 70-80°C to obtain a precursor;

[0016] The reaction process is as follows:

[0017]

[0018] Step B3: Add the precursor into the reactor, add the intermediate 3 at a speed of 150-200r / min and a temperature of 140-150°C, and react for 2-3h to obtain a modified precursor, mix the modified precursor, styrene, methyl methacrylate, potassium persulfate, sodium dodecylbenzene sulfonate and deionized water, and react for 3-5h at a speed of 300-500r / min and a temperature of 65-70°C to obtain a composite latex, mix the composite latex, methyl methacrylate, butyl acrylate, allyl alcohol glycidyl ether and potassium persulfate, and react for 4-6h at a speed of 300-500r / min and a temperature of 65-70°C to obtain a modified filler.

[0019] Furthermore, the molar ratio of octamethylcyclotetrasiloxane, tetramethyltetrasiloxane, 1,3-bis(3-aminopropyl)tetramethyldisiloxane and tetramethylammonium hydroxide in step B1 is 4:2:1:6, and the molar ratio of intermediate 1 and 1,2-epoxydodecane is 1:4.

[0020] Furthermore, the molar ratio of 4-formylphenylboronic acid and diaminobutene in step B2 is 2:1, the amount of triethylamine is 3% of the mass of 4-formylphenylboronic acid, the amount of KH570 is 2% of the mass of carbon nanotubes, the molar ratio of modified carbon nanotubes Si-H and intermediate 2 is 1:1, and the amount of chloroplatinic acid is 1‰ of the mass of intermediate 2.

[0021] Furthermore, the mass ratio of the precursor described in step B3 to the intermediate 3 is 3:1, the mass ratio of the modified precursor, styrene, methyl methacrylate, potassium persulfate, sodium dodecylbenzene sulfonate and deionized water in the preparation process of the composite latex is 5:20:5:0.4:1:15, and the mass ratio of the composite latex, methyl methacrylate, butyl acrylate, allyl alcohol glycidyl ether and potassium persulfate is 45:20:7:1:0.4.

[0022] Beneficial effects of the invention: The anti-bending data connection line disclosed by the invention is prepared by coating polyethylene on the surface of a conductor to form an insulating layer, a braided layer is arranged outside the insulating layer, a shielding layer is arranged outside the braided layer, and a modified resin is coated outside the shielding layer to form a protective layer, so as to prepare the anti-bending data connection line; the modified resin is prepared by reacting polypropylene glycol and isophorone diisocyanate as raw materials to form a polyurethane prepolymer, and 2-hydroxyethyl methacrylate is added for end-capping to prepare a modified polyurethane; PVC paste resin, modified polyurethane, allyl alcohol glycidyl ether, dioctyl phthalate and trimethylolpropane trimethacrylate are mixed, and then kneaded with modified filler and 4,4'-diaminodiphenylmethane to prepare a modified resin.

[0023] The modified filler is ring-opened with octamethylcyclotetrasiloxane and tetramethyltetrasiloxane as raw materials, and then polymerized with 1,3-bis(3-aminopropyl)tetramethyldisiloxane to obtain intermediate 1, and intermediate 1 is reacted with 1,2-epoxydodecane so that the amino group on intermediate 1 reacts with the epoxy group on 1,2-epoxydodecane to obtain intermediate 2, and 4-formylphenylboronic acid is reacted with diaminobutene so that the aldehyde group on 4-formylphenylboronic acid reacts with the amino group on diaminobutene to obtain intermediate 3, and carbon nanotubes are treated with KH570 so that double bonds are grafted on the surface of carbon nanotubes to obtain modified carbon nanotubes, and the modified Under the action of chloroplatinic acid, the double bonds on the modified carbon nanotubes and the Si-H bonds on the intermediate 2 are grafted to obtain a precursor. The precursor is reacted with the intermediate 3, so that the hydroxyl group on the precursor reacts with the boric acid group on the intermediate 3 to form a polyborosiloxane coating on the surface of the precursor to obtain a modified precursor. The modified precursor, styrene, methyl methacrylate, potassium persulfate, sodium dodecylbenzene sulfonate and deionized water are mixed for primary polymerization to obtain a composite latex. The composite latex, methyl methacrylate, butyl acrylate and allyl alcohol glycidyl ether are secondary polymerized to obtain a modified filler.

[0024] The modified filler is a special core-shell structure with carbon nanotubes as the hard core, polyborosiloxane coating as the soft layer, and polymethyl methacrylate as the hard shell. When the material is subjected to external force, the hard shell in the modified filler can cause the crack to deflect when it reaches the core-shell interface. The deflection of the crack increases the path of crack propagation, thereby absorbing more energy, and the hard shell undergoes plastic deformation near the crack tip. At the same time, the BO bond in the polyborosiloxane soft layer breaks. This plastic deformation and BO bond breaking can absorb energy, slow down the crack propagation speed, and improve the toughness of the modified resin. The modified resin is also a semi-interpenetrating grid structure, which can passivate the crack tip and reduce stress concentration, thereby reducing the crack propagation speed and increasing the toughness of the modified resin. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Embodiment 1: A method for preparing a bending-resistant data connection line, comprising the following steps:

[0027] Step A1: polypropylene glycol and isophorone diisocyanate are mixed, nitrogen is introduced for protection, dibutyltin dilaurate is added under stirring at a speed of 120 r / min and a temperature of 85° C., and the mixture is reacted for 2 h. Then, 2-hydroxyethyl methacrylate and hydroquinone are added and the mixture is reacted for 2 h to obtain a modified polyurethane;

[0028] Step A2: PVC paste resin, modified polyurethane, allyl alcohol glycidyl ether, dioctyl phthalate and trimethylolpropane trimethacrylate are mixed uniformly, placed at a temperature of 25° C. for 40 hours, heated to 150° C., kept warm for 10 minutes, placed in an internal mixer, modified filler and 4,4'-diaminodiphenylmethane are added, and the mixture is internally kneaded at a temperature of 170° C. for 20 minutes to obtain a modified resin;

[0029] Step A3: polyethylene is coated on the surface of the conductor to form an insulating layer, a braided layer is provided outside the insulating layer, a shielding layer is provided outside the braided layer, and a modified resin is coated outside the shielding layer to form a protective layer, so as to obtain a bending-resistant data connection line.

[0030] The molar ratio of polypropylene glycol, isophorone diisocyanate and 2-hydroxyethyl methacrylate in step A1 is 1:2.5:3.2, the amount of dibutyltin dilaurate is 2% of the total mass of polypropylene glycol, isophorone diisocyanate and 2-hydroxyethyl methacrylate, the amount of hydroquinone is 1‰ of 2-hydroxyethyl methacrylate, and the molecular weight of polypropylene glycol is 400.

[0031] The weight ratio of the PVC paste resin, modified polyurethane, allyl alcohol glycidyl ether, dioctyl phthalate, trimethylolpropane trimethacrylate, modified filler and 4,4'-diaminodiphenylmethane described in step A2 is 100:20:10:10:20:10:3, and the model of the PVC paste resin is PB1702.

[0032] The modified filler is prepared by the following steps:

[0033] Step B1: octamethylcyclotetrasiloxane, tetramethyltetrasiloxane, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, tetramethylammonium hydroxide and DMF were uniformly mixed, and reacted at a speed of 150 r / min and a temperature of 105° C. for 2 h to obtain intermediate 1; intermediate 1, 1,2-epoxydodecane and DMF were uniformly mixed, and reacted at a speed of 120 r / min, a temperature of 60° C. and a pH value of 10 for 3 h to obtain intermediate 2;

[0034] Step B2: 4-formylphenylboronic acid, diaminobutene, triethylamine and DMF were mixed, and the mixture was reacted for 3 hours at a speed of 200 r / min and a temperature of 20°C to obtain intermediate 3. Carbon nanotubes were dispersed in ethanol, and KH570 and deionized water were added under stirring at a speed of 200 r / min and a temperature of 60°C to react for 1 hour to obtain modified carbon nanotubes. The modified carbon nanotubes, intermediate 2, chloroplatinic acid and DMF were uniformly mixed, and the mixture was reacted for 3 hours at a speed of 120 r / min and a temperature of 70°C to obtain a precursor.

[0035] Step B3: Add the precursor into the reactor, add intermediate 3 at a speed of 150r / min and a temperature of 140°C, and react for 2h to obtain a modified precursor; mix the modified precursor, styrene, methyl methacrylate, potassium persulfate, sodium dodecylbenzene sulfonate and deionized water, and react for 3h at a speed of 300r / min and a temperature of 65°C to obtain a composite latex; mix the composite latex, methyl methacrylate, butyl acrylate, allyl alcohol glycidyl ether and potassium persulfate, and react for 4h at a speed of 300r / min and a temperature of 65°C to obtain a modified filler.

[0036] The molar ratio of octamethylcyclotetrasiloxane, tetramethyltetrasiloxane, 1,3-bis(3-aminopropyl)tetramethyldisiloxane and tetramethylammonium hydroxide described in step B1 is 4:2:1:6, and the molar ratio of intermediate 1 and 1,2-epoxydodecane is 1:4.

[0037] The molar ratio of 4-formylphenylboronic acid and diaminobutene described in step B2 is 2:1, the amount of triethylamine used is 3% of the mass of 4-formylphenylboronic acid, the amount of KH570 used is 2% of the mass of carbon nanotubes, the molar ratio of modified carbon nanotubes Si-H and intermediate 2 is 1:1, and the amount of chloroplatinic acid used is 1‰ of the mass of intermediate 2.

[0038] The mass ratio of the precursor and intermediate 3 described in step B3 is 3:1. The mass ratio of the modified precursor, styrene, methyl methacrylate, potassium persulfate, sodium dodecylbenzene sulfonate and deionized water in the preparation process of the composite latex is 5:20:5:0.4:1:15. The mass ratio of the composite latex, methyl methacrylate, butyl acrylate, allyl alcohol glycidyl ether and potassium persulfate is 45:20:7:1:0.4.

[0039] Embodiment 2: A method for preparing a bending-resistant data connection line, comprising the following steps:

[0040] Step A1: polypropylene glycol and isophorone diisocyanate are mixed, nitrogen is introduced for protection, dibutyltin dilaurate is added under stirring at a speed of 120 r / min and a temperature of 88° C., and the mixture is reacted for 3 hours. Then, 2-hydroxyethyl methacrylate and hydroquinone are added and the mixture is reacted for 3 hours to obtain a modified polyurethane;

[0041] Step A2: PVC paste resin, modified polyurethane, allyl alcohol glycidyl ether, dioctyl phthalate and trimethylolpropane trimethacrylate are mixed uniformly, placed at a temperature of 25° C. for 40 hours, heated to 155° C., kept warm for 10 minutes, placed in an internal mixer, modified filler and 4,4'-diaminodiphenylmethane are added, and the mixture is internally kneaded at a temperature of 175° C. for 25 minutes to obtain a modified resin;

[0042] Step A3: polyethylene is coated on the surface of the conductor to form an insulating layer, a braided layer is provided outside the insulating layer, a shielding layer is provided outside the braided layer, and a modified resin is coated outside the shielding layer to form a protective layer, so as to obtain a bending-resistant data connection line.

[0043] The molar ratio of polypropylene glycol, isophorone diisocyanate and 2-hydroxyethyl methacrylate in step A1 is 1:2.5:3.2, the amount of dibutyltin dilaurate is 2% of the total mass of polypropylene glycol, isophorone diisocyanate and 2-hydroxyethyl methacrylate, the amount of hydroquinone is 1‰ of 2-hydroxyethyl methacrylate, and the molecular weight of polypropylene glycol is 400.

[0044] The weight ratio of the PVC paste resin, modified polyurethane, allyl alcohol glycidyl ether, dioctyl phthalate, trimethylolpropane trimethacrylate, modified filler and 4,4'-diaminodiphenylmethane described in step A2 is 110:25:13:11:25:13:4, and the model of the PVC paste resin is PB1702.

[0045] The modified filler is prepared by the following steps:

[0046] Step B1: octamethylcyclotetrasiloxane, tetramethyltetrasiloxane, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, tetramethylammonium hydroxide and DMF were uniformly mixed, and reacted at a speed of 150 r / min and a temperature of 110° C. for 2 h to obtain intermediate 1; intermediate 1, 1,2-epoxydodecane and DMF were uniformly mixed, and reacted at a speed of 150 r / min, a temperature of 65° C. and a pH value of 10 for 4 h to obtain intermediate 2;

[0047] Step B2: 4-formylphenylboronic acid, diaminobutene, triethylamine and DMF were mixed, and the mixture was reacted at a speed of 200 r / min and a temperature of 25°C for 4 hours to obtain intermediate 3. Carbon nanotubes were dispersed in ethanol, and KH570 and deionized water were added under stirring at a speed of 200 r / min and a temperature of 65°C for 1.5 hours to obtain modified carbon nanotubes. The modified carbon nanotubes, intermediate 2, chloroplatinic acid and DMF were uniformly mixed, and the mixture was reacted at a speed of 120 r / min and a temperature of 75°C for 4 hours to obtain a precursor.

[0048] Step B3: Add the precursor into the reactor, add intermediate 3 at a speed of 200 r / min and a temperature of 145°C, and react for 2 hours to obtain a modified precursor; mix the modified precursor, styrene, methyl methacrylate, potassium persulfate, sodium dodecylbenzene sulfonate and deionized water, and react for 4 hours at a speed of 300 r / min and a temperature of 70°C to obtain a composite latex; mix the composite latex, methyl methacrylate, butyl acrylate, allyl alcohol glycidyl ether and potassium persulfate, and react for 5 hours at a speed of 300 r / min and a temperature of 70°C to obtain a modified filler.

[0049] The molar ratio of octamethylcyclotetrasiloxane, tetramethyltetrasiloxane, 1,3-bis(3-aminopropyl)tetramethyldisiloxane and tetramethylammonium hydroxide described in step B1 is 4:2:1:6, and the molar ratio of intermediate 1 and 1,2-epoxydodecane is 1:4.

[0050] The molar ratio of 4-formylphenylboronic acid and diaminobutene described in step B2 is 2:1, the amount of triethylamine used is 3% of the mass of 4-formylphenylboronic acid, the amount of KH570 used is 2% of the mass of carbon nanotubes, the molar ratio of modified carbon nanotubes Si-H and intermediate 2 is 1:1, and the amount of chloroplatinic acid used is 1‰ of the mass of intermediate 2.

[0051] The mass ratio of the precursor and intermediate 3 described in step B3 is 3:1. The mass ratio of the modified precursor, styrene, methyl methacrylate, potassium persulfate, sodium dodecylbenzene sulfonate and deionized water in the preparation process of the composite latex is 5:20:5:0.4:1:15. The mass ratio of the composite latex, methyl methacrylate, butyl acrylate, allyl alcohol glycidyl ether and potassium persulfate is 45:20:7:1:0.4.

[0052] Embodiment 3: A method for preparing a bending-resistant data connection line, comprising the following steps:

[0053] Step A1: polypropylene glycol and isophorone diisocyanate are mixed, nitrogen is introduced for protection, dibutyltin dilaurate is added under stirring at a speed of 150 r / min and a temperature of 90° C., and the mixture is reacted for 3 hours. Then, 2-hydroxyethyl methacrylate and hydroquinone are added and the mixture is reacted for 4 hours to obtain a modified polyurethane;

[0054] Step A2: PVC paste resin, modified polyurethane, allyl alcohol glycidyl ether, dioctyl phthalate and trimethylolpropane trimethacrylate are mixed uniformly, placed at a temperature of 30° C. for 45 hours, heated to 155° C., kept warm for 15 minutes, placed in an internal mixer, modified filler and 4,4'-diaminodiphenylmethane are added, and the mixture is internally kneaded at a temperature of 180° C. for 30 minutes to obtain a modified resin;

[0055] Step A3: polyethylene is coated on the surface of the conductor to form an insulating layer, a braided layer is provided outside the insulating layer, a shielding layer is provided outside the braided layer, and a modified resin is coated outside the shielding layer to form a protective layer, so as to obtain a bending-resistant data connection line.

[0056] The molar ratio of polypropylene glycol, isophorone diisocyanate and 2-hydroxyethyl methacrylate in step A1 is 1:2.5:3.2, the amount of dibutyltin dilaurate is 2% of the total mass of polypropylene glycol, isophorone diisocyanate and 2-hydroxyethyl methacrylate, the amount of hydroquinone is 1‰ of 2-hydroxyethyl methacrylate, and the molecular weight of polypropylene glycol is 400.

[0057] The weight ratio of the PVC paste resin, modified polyurethane, allyl alcohol glycidyl ether, dioctyl phthalate, trimethylolpropane trimethacrylate, modified filler and 4,4'-diaminodiphenylmethane described in step A2 is 120:30:15:12:30:15:5, and the model of the PVC paste resin is PB1702.

[0058] The modified filler is prepared by the following steps:

[0059] Step B1: octamethylcyclotetrasiloxane, tetramethyltetrasiloxane, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, tetramethylammonium hydroxide and DMF were mixed evenly, and reacted at a speed of 200 r / min and a temperature of 110° C. for 3 h to obtain intermediate 1; intermediate 1, 1,2-epoxydodecane and DMF were mixed evenly, and reacted at a speed of 150 r / min, a temperature of 70° C. and a pH value of 11 for 5 h to obtain intermediate 2;

[0060] Step B2: 4-formylphenylboronic acid, diaminobutene, triethylamine and DMF were mixed, and the mixture was reacted at a speed of 300 r / min and a temperature of 25°C for 5 hours to obtain intermediate 3. Carbon nanotubes were dispersed in ethanol, and KH570 and deionized water were added under stirring at a speed of 300 r / min and a temperature of 70°C for 1.5 hours to obtain modified carbon nanotubes. The modified carbon nanotubes, intermediate 2, chloroplatinic acid and DMF were uniformly mixed, and the mixture was reacted at a speed of 150 r / min and a temperature of 80°C for 5 hours to obtain a precursor.

[0061] Step B3: Add the precursor into the reactor, add intermediate 3 at a speed of 200 r / min and a temperature of 150°C, and react for 3 hours to obtain a modified precursor; mix the modified precursor, styrene, methyl methacrylate, potassium persulfate, sodium dodecylbenzene sulfonate and deionized water, and react for 5 hours at a speed of 500 r / min and a temperature of 70°C to obtain a composite latex; mix the composite latex, methyl methacrylate, butyl acrylate, allyl alcohol glycidyl ether and potassium persulfate, and react for 6 hours at a speed of 500 r / min and a temperature of 70°C to obtain a modified filler.

[0062] The molar ratio of octamethylcyclotetrasiloxane, tetramethyltetrasiloxane, 1,3-bis(3-aminopropyl)tetramethyldisiloxane and tetramethylammonium hydroxide described in step B1 is 4:2:1:6, and the molar ratio of intermediate 1 and 1,2-epoxydodecane is 1:4.

[0063] The molar ratio of 4-formylphenylboronic acid and diaminobutene described in step B2 is 2:1, the amount of triethylamine used is 3% of the mass of 4-formylphenylboronic acid, the amount of KH570 used is 2% of the mass of carbon nanotubes, the molar ratio of modified carbon nanotubes Si-H and intermediate 2 is 1:1, and the amount of chloroplatinic acid used is 1‰ of the mass of intermediate 2.

[0064] The mass ratio of the precursor and intermediate 3 described in step B3 is 3:1. The mass ratio of the modified precursor, styrene, methyl methacrylate, potassium persulfate, sodium dodecylbenzene sulfonate and deionized water in the preparation process of the composite latex is 5:20:5:0.4:1:15. The mass ratio of the composite latex, methyl methacrylate, butyl acrylate, allyl alcohol glycidyl ether and potassium persulfate is 45:20:7:1:0.4.

[0065] Comparative Example 1: Compared with Example 1, PVC paste resin, modified filler and 4,4'-diaminodiphenylmethane were added into an internal mixer and subjected to internal mixing at a temperature of 170° C. to obtain a modified resin.

[0066] Comparative Example 2: Compared with Example 1, this comparative example uses carbon nanotubes instead of the modified filler, and the other steps are the same.

[0067] Comparative Example 3: Compared with Example 1, this comparative example uses modified carbon nanotubes instead of modified precursor, and the other steps are the same.

[0068] Comparative Example 4: Compared with Example 1, modified polyurethane and modified filler were not added in this comparative example, and the remaining steps were the same.

[0069] The modified resins obtained in Examples 1-3 and Comparative Examples 1-4 were made into Type II specimens according to the standard of GB / T1040-2018, and the tensile strength was tested at a tensile rate of 5 mm / min. Notched Type A specimens were made according to GB / T1843-2008 to test the impact strength. The test results are shown in Table 1 below.

[0070] Table 1

[0071]

[0072] It can be seen from Table 1 above that the present application has good toughness.

[0073] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a bending-resistant data connection line, characterized in that: The specific steps include: Step A1: polypropylene glycol and isophorone diisocyanate are mixed, nitrogen is introduced for protection, dibutyltin dilaurate is added after stirring, and after reaction, 2-hydroxyethyl methacrylate and hydroquinone are added and reacted to obtain a modified polyurethane; Step A2: mixing PVC paste resin, modified polyurethane, allyl alcohol glycidyl ether, dioctyl phthalate and trimethylolpropane trimethacrylate, placing the mixture in an internal mixer, adding modified filler and 4,4'-diaminodiphenylmethane, and performing internal mixing to obtain a modified resin; Step A3: polyethylene is coated on the surface of the conductor to form an insulating layer, a braided layer is provided outside the insulating layer, a shielding layer is provided outside the braided layer, and a modified resin is coated outside the shielding layer to form a protective layer, so as to obtain a bending-resistant data connection line; The modified filler is prepared by the following steps: Step B1: octamethylcyclotetrasiloxane, tetramethyltetrasiloxane, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, tetramethylammonium hydroxide and DMF are uniformly mixed and reacted to obtain intermediate 1; intermediate 1, 1,2-epoxydodecane and DMF are mixed and reacted to obtain intermediate 2; Step B2: 4-formylphenylboronic acid, diaminobutene, triethylamine and DMF are mixed and reacted to obtain intermediate 3, carbon nanotubes are dispersed in ethanol, stirred and KH570 and deionized water are added to react to obtain modified carbon nanotubes, and the modified carbon nanotubes, intermediate 2, chloroplatinic acid and DMF are mixed and reacted to obtain a precursor; Step B3: Add the precursor to a reactor, add intermediate 3, react to obtain a modified precursor, mix the modified precursor, styrene, methyl methacrylate, potassium persulfate, sodium dodecylbenzene sulfonate and deionized water, react to obtain a composite latex, mix the composite latex, methyl methacrylate, butyl acrylate, allyl alcohol glycidyl ether and potassium persulfate, react to obtain a modified filler.

2. The method for preparing a bending-resistant data connection line according to claim 1, characterized in that: The molar ratio of polypropylene glycol, isophorone diisocyanate and 2-hydroxyethyl methacrylate in step A1 is 1:2.5:3.

2.

3. The method for preparing a bending-resistant data connection line according to claim 1, characterized in that: The weight ratio of the PVC paste resin, modified polyurethane, allyl alcohol glycidyl ether, dioctyl phthalate, trimethylolpropane trimethacrylate, modified filler and 4,4'-diaminodiphenylmethane described in step A2 is 100-120:20-30:10-15:10-12:20-30:10-15:3-5.

4. The method for preparing a bending-resistant data connection line according to claim 1, characterized in that: The molar ratio of octamethylcyclotetrasiloxane, tetramethyltetrasiloxane, 1,3-bis(3-aminopropyl)tetramethyldisiloxane and tetramethylammonium hydroxide described in step B1 is 4:2:1:6, and the molar ratio of intermediate 1 and 1,2-epoxydodecane is 1:

4.

5. The method for preparing a bending-resistant data connection line according to claim 1, characterized in that: The molar ratio of 4-formylphenylboronic acid and diaminobutene in step B2 is 2:1, the amount of KH570 used is 2% of the mass of the carbon nanotubes, and the molar ratio of the Si-H bonds on the modified carbon nanotubes to the intermediate 2 is 1:

1.

6. The method for preparing a bending-resistant data connection line according to claim 1, characterized in that: The mass ratio of the precursor and intermediate 3 described in step B3 is 3:

1. The mass ratio of the modified precursor, styrene, methyl methacrylate, potassium persulfate, sodium dodecylbenzene sulfonate and deionized water in the preparation process of the composite latex is 5:20:5:0.4:1:

15. The mass ratio of the composite latex, methyl methacrylate, butyl acrylate, allyl alcohol glycidyl ether and potassium persulfate is 45:20:7:1:0.

4.

7. A bending-resistant data cable, characterized in that: Prepared according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Polyurethane acrylate elastomer as well as preparation method and application thereof

    CN116948205A

  • Flexible medical cable for minimally invasive radiofrequency ablation treatment and preparation method thereof

    CN118299111A

  • Solid coaxial cable

    CN201904101U